Development and performance evaluation of a tractor operated Chinese potato harvester - T. Krishnakumar; M.S. Sajeev; C. Pradeepika; M. Velmurugan; C. Thangamani (JOURNAL OF ROOT CROPS, 2024)
Manual harvesting of Chinese potato tubers is labour intensive, time consuming and tedious. An average of 100 female labourers and 20 male labourers are needed to harvest one acre of Chinese potato tubers. To mitigate labour shortages and to reduce harvesting costs, a tractor operated prototype Chinese potato harvester has been designed and developed to harvest the tubers grown in ridge and furrow system. The harvester comprises of a main frame, digging system, discharge system, power transmission system and transport system. It can cover three ridges with a spacing of 30 cm and a depth of operation of 15 cm. The performance evaluation of the developed unit was conducted, and the operational parameters were standardized. The digging unit of the harvester was tested with different treatment combinations of blade geometries viz., inverted V shape, crescent shape and straight type blade at different rake angles of 15, 20 and 25° and at different forward operating speeds of 1.5, 2.0 and 2.5 km h-1. The effects due to these parameters were optimized based on performances parameters viz., digging efficiency, per cent damage and fuel consumption by numerical optimization technique. The maximum digging efficiency of 97.28 per cent was noticed for inverted V type digging blade, whereas the lowest of 82.37 per cent was obtained for straight shaped blade. The least percent damage of 3.42 per cent was for the inverted V shape blade and the highest of 9.91 per cent was recorded for straight blade. Among the different types of blade geometry, the maximum (6.24 l h-1) and minimum (4.75 l h-1) fuel consumptions were obtained for straight blade and inverted V shape blade, respectively. The cost per hectare of harvesting using the developed harvester was determined to be ` 18,400/- per hectare compared to ` 1,12,500/- for harvesting manually, with a cost savings ` 94,100/- per hectare. Keywords: Chinese potato, Harvester, Manual harvesting, Labour shortage, Mechanical harvesting